2008
DOI: 10.1002/glia.20827
|View full text |Cite
|
Sign up to set email alerts
|

P2 receptor‐mediated stimulation of the PI3‐K/Akt‐pathway in vivo

Abstract: ATP acts as a growth factor as well as a toxic agent by stimulating P2 receptors. The P2 receptor-activated signaling cascades mediating cellular growth and cell survival after injury are only incompletely understood. Therefore, the aim of the present study was to identify the role of the phosphoinositide 3 kinase (PI3-K/Akt) and the mitogen-activated protein kinase/extracellular signal regulated protein kinase (MAPK/ERK) pathways in P2Y receptor-mediated astrogliosis after traumatic injury and after microinfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…Additionally, ATP and P2 receptors were shown to increase endothelial cell migration and adhesion in a PI3 kinase-dependent manner (17). Similarly, in vivo microinjections of ATP into the nucleus accumbens activated the PI3 kinase/Akt signaling pathway, leading to neuron proliferation, and this was blocked by the P2 receptor antagonist PPADS (8).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, ATP and P2 receptors were shown to increase endothelial cell migration and adhesion in a PI3 kinase-dependent manner (17). Similarly, in vivo microinjections of ATP into the nucleus accumbens activated the PI3 kinase/Akt signaling pathway, leading to neuron proliferation, and this was blocked by the P2 receptor antagonist PPADS (8).…”
Section: Discussionmentioning
confidence: 98%
“…20,57 ATP released by astrocytes activates AKT and ERK signaling, resulting in gliosis following traumatic brain injury. 58,59 Injury-triggered extracellular ATP also affects microglial response following brain injury. 60,61 We have identified that injury-triggered lysosome exocytosis causes secretion of acid sphingomyelinase (ASM), which is needed for cell membrane repair.…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is most probable that signaling is mediated by the P2Y receptor signal transduction pathway. As G-protein-coupled receptors, P2Y family members activate phospholipase C (PLC) to hydrolyze phosphatidylinositol 4,5-bisphosphate to 1,2-diacylglycerol and inositol triphosphate, subsequently causing the release of intracellular Ca 2+ and the activation of protein kinase C (PKC), as well as downstream signaling cascades such as those mediated by mitogen-activated protein kinase and PI3K (Franke et al, 2009;Thelen and Didichenko, 1997). In support of an involvement of this pathway, we observed that the PLC inhibitor U73122 potentiated, whereas PLC activator m-3M3FBS suppressed AMPK activation (supplementary material Fig.…”
Section: +mentioning
confidence: 99%